Navigating Biologics Regulation: A Deep Dive into Australian Compliance - Saji, Nayana; Kethareshwara Sujatha, Deeksha; Veeranna, Balamuralidhara (Asian Journal of Biological and Life Sciences)
Biologics are at the forefront of therapeutic breakthroughs, marking a paradigm change in medical therapies in an ever-evolving field. Complex biological products known as biologics are used to treat a variety of illnesses and disorders and both their development and marketing are governed by strict rules. Australia’s regulatory agency, the Therapeutic Goods Administration (TGA), employs rigorous pre-approval assessments and post-marketing surveillance to guarantee the effectiveness, safety and quality of biologics. The article concludes that Australia’s regulatory guidelines for biologics are intended to safeguard the general public’s health and guarantee that patients receive reliable medical care.
Keywords: Biologics; TGA; Post-marketing surveillance; Quality; Safety; Efficacy